Association between antibiotic consumption and colon and rectal cancer development in older individuals: A territory‐wide study. (29th April 2022) - Cheung, Ka Shing; Chan, Esther W.; Tam, Anthony; Wong, Irene O. L.; Seto, Wai Kay; Hung, Ivan F. N.; Wong, Ian C. K.; Leung, Wai K.
Abstract: Background: Antibiotics may alter colorectal cancer (CRC) risk due to gut dysbiosis. We aimed to study the specific and temporal effects of various antibiotics on CRC development in older individuals. Methods: This was a territory‐wide retrospective cohort study. Subjects aged 60 years and older who did not have CRC diagnosed on screening/diagnostic colonoscopy diagnosed between 2005 and 2013 were recruited. Exclusion criteria were history of CRC, colectomy, inflammatory bowel disease, and CRC diagnosed within 6 months of index colonoscopy. Exposure was use of any antibiotics up to 5 years before colonoscopy. The primary outcomes were CRC diagnosed >6 m after colonoscopy. Covariates were patient demographics, history of colonic polyps/polypectomy, concomitant medication use (NSAIDs, COX‐2 inhibitors, aspirin, and statins), and performance of endoscopy centers (colonoscopy volume and polypectomy rate). Stratified analysis was conducted according to nature of antibiotics and location of cancer. Results: Ninety seven thousand one hundred and sixty‐two eligible subjects (with 1026 [1.0%] cases of CRC) were identified, 58, 704 (60.4%) of whom were exposed to antibiotics before index colonoscopy. Use of antibiotics was associated with a lower risk of cancer in rectum (adjusted hazard ratio [aHR]: 0.64, 95% CI: 0.54–0.76), but a higher risk of cancer in proximal colon (aHR: 1.63, 95%CI: 1.15–2.32). These effects differed as regards the anti‐anaerobic/anti‐aerobic activity, narrow‐/broad‐spectrum, and administration route of antibiotics. Conclusions: Antibiotics had divergent effects on CRC development in older subjects, which varied according to the location of cancer, antibiotic class, and administration route. Abstract : Whether antibiotics modify colorectal cancer (CRC) risk remains controversial. In this study involving 97, 162 patients aged ≥60 years who had index colonoscopy negative for CRC, antibiotic use was associated with 36% lower rectal cancer risk, 63% higher proximal colon cancer risk and neutral effect on distal colon risk. Our findings provide insight into the differential effects of various antibiotics on CRC development in older patients, which varied according to cancer locations, classes of antibiotics and routes of administration.